Material Characterization of a Dielectric Elastomer for the Design of a Linear Actuator - Helal, Alexander Tristan (Université d'Ottawa / University of Ottawa, 2017)
Electrical motors and/or hydraulics and pneumatics cylinders are commonly used methods of actuation in mechanical systems. Over the last two decades, due to arising market needs, novel self-independent mobile systems such as mobility assistive devices have emerged with the help of new advancements in technology. The actuation criteria for these devices differ greatly from typical mechanical systems, which has made the implementation of classical actuators difficult within modern assistive devices. Among the numerous challenges, limited energy storage capabilities by mobile systems have restricted their achievable operational time. Furthermore, new expectations for device weight and volume, as well as actuator structural compliance, have added to this quandary. Electroactive polymers, a category of smart materials, have emerged as a strong contender for the use in low-cost efficient actuators. They have demonstrated great potential in soft robotic and assistive device/prosthetic applications due to their actuation potential and similar mechanical behaviour to human skeletal muscles. Dielectric Elastomers, in particular, have shown very promising properties for these types of applications. Their structures have shown large achievable deformation, while remaining light-weight, mechanically efficient, and low-cost. This thesis aims to characterize, and model the behaviour of 3MTM VHB polyacrylic dielectric elastomer, in order to establish a foundation for its implementation in a proposed novel linear actuator concept. In this thesis, a comprehensive experimental evaluation is accomplished, which resulted in the better understanding of the elastomer’s biaxial mechanical and electro-mechanically coupled behaviours. Subsequently, a constitutive biaxial mechanical model was derived in order to provide a predictive design equation for future actuator development. This model proved effective in providing a predictive tool for the biaxial mechanical tensile response of the material. Finally, a simplified prototype was devised as a proof of concept. This first iteration applied experimental findings to validate the working principles behind the proposed actuator design. The results confirmed the proof of concept, through achieved reciprocal linear motion, and provided insight into the design considerations for prototype optimization and final actuator development.
Keywords: Smart Material; Dielectric Elastomer; Actuation; Mobility; Electroactive Polymer; Biaxial; Modelling; VHB